Identification, Characterization, and Expression of a PRQFVamide-Related Peptide in Cephalopod Sepiella japonica - Qiu, Jia-yin; Zheng, Li-bing; Chi, Chang-feng (Frontiers in Marine Science, 2022)
Neuropeptides, as neurotransmitters and neuromodulators, have a variety of physiological functions in the mollusk. Here, a PRQFVamide-related peptide gene was cloned from cuttlefish Sepiella japonica (designated as SjPRQFVRP, GenBank Accession No: OK999997). The full length of SjPRQFVRP is 1748 bp, including an open reading frame (ORF) of 738 bp encoding 245 amino acids. The putative precursor protein comprises one signal peptide and four different mature pentapeptides: fourteen copies of PMEFLamide, three copies of RMEFLamide, one copy of AMEFLamide and GMEFLamide. Multiple alignments showed SjPRQFVRP shared 71% identity with that of Octopus vulgaris and supported the phylogenetic analysis. The spatio-temporal expression pattern showed that SjPRQFVRP mRNA was widely expressed among the thirteen tissues and primarily abundantly expressed in the brain and optic lobe during the whole development stage. In situ hybridization data indicated that SjPRQFVRP was detected in the vertical lobe, subvertical lobe, anterior basal lobe, anterior pedal lobe, and optic lobes of the brain. Subcellular localization analysis revealed that the SjPRQFVRP protein was localized in the cytoplasm of HEK293 cells. Collectively, the results will provide a foundation for further exploring the mechanism of SjPRQFVRP function in cephalopods.